Skating through pregnancy and motherhood: A narrative analysis of digital stories of elite figure skating expectant mothers. (March 2022) - McGannon, Kerry R.; Graper, Sydney; McMahon, Jenny
Abstract: Objectives: Although research on elite sport and motherhood is growing, more research is needed to understand the narratives that shape their identities and lives. We sought to build on sport psychology research centralizing the media as naturalistic data resources to explore elite athlete mother identity in cultural context. The specific aim was to explore how elite athlete identities are portrayed during pregnancy on Instagram. Design: Two high profile elite figure skating expectant mothers' (i.e., Meagan Duhamel and Aljona Savchenko) Instagram posts were the focus of a dialogical narrative analysis (DNA) grounded in relativist narrative inquiry. Two research questions were explored: 1. how do expectant athlete mothers portray themselves in big and small stories, and 2. what are the implications (e.g., psychosocial, behavioural) of identity meanings portrayed in digital stories? Results: DNA of 122 posts (n = 82 for Duhamel, n = 40 for Savchenko) identified a key big story: (re)configuring ideal pregnancy. Four small stories fed into fluid meanings of 'ideal pregnancy' and ways of 'doing pregnancy' linked to self-identity portrayals: documenting the growing life, baby bumps on display, Olympic dreams/journeys and living the good life through leisure. Consumerism was shown to thread small stories. These findings show contradictions of motherhood meanings and body ideals (e.g., feminine, athletic) vs realities (e.g., tired, sore), linked to actions (e.g., skating during pregnancy, promoting products or athlete brand), in good mother and biomedical narratives. Conclusions: A big and small story approach grounded in narrative inquiry holds value to learn more about the digital landscape's role in shaping athlete expectant mother self-identities. Future research exploring social media (e.g., Twitter, Facebook) may expand intertextual understanding of athlete mothers' identities and lives. Highlights: Understandings of elite athletes and pregnancy is extended studying digital stories. A central 'big story' of ideal pregnancy linked to doing pregnancy is identified. Three small stories feed into, and reconfigure, 'ideal pregnancy' meanings. Insight into identity meanings of pregnancy, motherhood and sport is gained.